2014
DOI: 10.11604/pamj.2014.19.262.4512
|View full text |Cite
|
Sign up to set email alerts
|

La fibroscopie digestive haute chez 2795 patients au centre hospitalier universitaire-campus de Lomé: les particularités selon le sexe

Abstract: IntroductionNotre étude consistera à rapporter les indications et les lésions objectivées à la fibroscopie digestive haute et relever les particularités selon le sexe.MéthodesÉtude rétrospective, descriptive sur des résultats de compte-rendu de la fibroscopie digestive haute menée en unité d'endoscopie digestive du service d'hépato-gastro-entérologie du CHU Campus de Lomé du 15 Mai 2009 au 31 Décembre 2013.RésultatsLa fibroscopie digestive haute a été réalisée chez 2795 patients dont 1188 hommes et 1607 femmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
4
7
1
Order By: Relevance
“…Our result was higher than those of other authors [5] [9] who reported frequencies of 5.9% and 6.97%, but remained near the 10.8% of Taye [14] in Ethiopia. Attia Y.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Our result was higher than those of other authors [5] [9] who reported frequencies of 5.9% and 6.97%, but remained near the 10.8% of Taye [14] in Ethiopia. Attia Y.…”
Section: Discussioncontrasting
confidence: 92%
“…It remains below the 60.68% reported by Lawson-Ananissoh L.M [9]. in Lomé, to 58.9% of Stephen in Ghana, and 72.9% of Peghini M [20].…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…We found a female predominance as in the Togolese and *Others: ATDC gastrectomy (n = 3), cardiomyotomy (n = 1), gastric ulcer (n = 6), polyp (n = 1), cholestasis (n = 1). [4]; Alandry (49.5%) [5] and Ismaila (39.3%) [6]. This could be explained by the frequency of bile reflux 53.5% of cases in our study.…”
Section: Discussionmentioning
confidence: 52%